2022
DOI: 10.1063/5.0086370
|View full text |Cite
|
Sign up to set email alerts
|

Convective dissolution of carbon dioxide in two- and three-dimensional porous media: The impact of hydrodynamic dispersion

Abstract: Convective dissolution is the process by which CO2 injected in geological formations dissolves into the aqueous phase and thus remains stored perennially by gravity. It can be modeled by buoyancy-coupled Darcy flow and solute transport. The transport equation should include a diffusive term accounting for hydrodynamic dispersion, wherein the effective diffusion coefficient is proportional to the local interstitial velocity. We investigate the impact of the hydrodynamic dispersion tensor on convective dissoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
(90 reference statements)
2
10
0
Order By: Relevance
“…Most studies on convective dissolution did not consider this effect. Much of the focus in systems, which do incorporate dispersion, was given to the effect of dispersion on the onset of convection (Dhar et al., 2022; Ghesmat et al., 2011; Hassanzadeh et al., 2009; Hidalgo & Carrera, 2009). While Ghesmat et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on convective dissolution did not consider this effect. Much of the focus in systems, which do incorporate dispersion, was given to the effect of dispersion on the onset of convection (Dhar et al., 2022; Ghesmat et al., 2011; Hassanzadeh et al., 2009; Hidalgo & Carrera, 2009). While Ghesmat et al.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the focus in systems, which do incorporate dispersion, was given to the effect of dispersion on the onset of convection (Dhar et al, 2022;Ghesmat et al, 2011;Hassanzadeh et al, 2009;Hidalgo & Carrera, 2009). While Ghesmat et al (2011), Hidalgo and Carrera (2009), and Dhar et al (2022), considered only the effect of hydrodynamic dispersion, Hassanzadeh et al (2009) also considered the effect of natural groundwater flow. Although the findings of these studies did not appear to coincide, Wen et al (2018) reported that the source of this discrepancy was due to different choices of scaling and that dispersion generally delays the onset time and decreases the dissolution flux.…”
mentioning
confidence: 99%
“…Convective dissolution has also been extensively studied by means of 2D simulations where the physical processes at stake are integrated over a ‘mesoscopic’ Darcy scale; 17–21 a few 3D numerical studies have also been performed, 22 including, recently, simulations where hydrodynamic dispersion is accounted for. 23…”
Section: Introductionmentioning
confidence: 99%
“…Convective dissolution has also been extensively studied by means of 2D simulations where the physical processes at stake are integrated over a 'mesoscopic' Darcy scale; [17][18][19][20][21] a few 3D numerical studies have also been performed, 22 including, recently, simulations where hydrodynamic dispersion is accounted for. 23 In this context, the use of patterned Hele-Shaw cells (i.e., quasi-2D porous media) is a method allowing both for heterogeneous pore flow and the pore scale measurement of the concentration field of the dissolved CO 2 , and hence, of the dissolution flux. In this article, we depict the design and the manufacturing process of such bi-dimensional porous micromodels (MM) which can allow for a direct and rigorous study of the role of pore scale flow and solute mixing in the solubility trapping of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation